12.03 Acute neurology: a two week snapshot in a district general hospital. Issue 12 (14th November 2019) - Kanagaratnam, Meneka; Boodhoo, Ajay; MacDonald, Bridget; Nitkunan, Arani
Abstract : Neurological illnesses are a common cause of hospital admissions, yet most patients are not primarily managed by neurologists. Acute neurology services also vary across the UK. During a 2 week period in a district general hospital with a 5 day inreaching neurological service (a consultant delivered service with a neurology nurse coordinator but no inpatient beds), the number of patients admitted with a neurological problem, as well as the proportion of those patients who were seen by the hyperacute neurology team was assessed by reviewing the diagnostic codes. It was established there was a total of 2242 admissions during the study period, and of those, 491 (22%) had neurological codes. Careful analysis of the 491 hospital electronic records revealed that 229 (10%) were truly neurologically relevant. Of those, 14% patients had a neurological opinion – despite a relatively comprehensive service (compared to many other district general hospitals), only a small proportion of acute neurology is being seen by neurologists.